Complete staining of nerve fiber and myoneural junctions with acetylthiocholine and silver - Boaro, S. N.; Gregorio, E. A. (Williams & Wilkins, 1997)
We describe a combined stain for simultaneous demonstration of the preterminal axons and cholinesterase activity at myoneural junctions of mammalian muscles. This technique employs acetylthiocholine iodide as the substrate for cholinesterase activity and silver nitrate impregnation of preterminal axons. The procedure is rapid, simple and uses fresh muscles. Intramuscular nerves, preterminal axons and myoneural junctions are stained simultaneously brown or black with minimal background staining of connective tissue and muscle fibers.
Keywords: acetylthiocholine; myoneural junctions; preterminal axons; silver impregnation